Correction to: Prevalence and Antibiotic Resistance Pattern of Citrobacter freundii Isolated from A Burn Center - Zahra Norouzi Bazgir; Hamid reza Goli; Bahman Mirzaei (Journal of Mazandaran University of Medical Sciences, 2019)
In the article published in volume 29, issue 174, 2019, the affiliation and surname of Zahra Norouzi bazgir was published incorrectly, which is now corrected.